The effect of doping variation on band gap energy and crystal structure of Biochar/TiO2 thin layer. Issue 1 (January 2021) - Fahyuan, H D; Deswardani, F; Nurhidayah, N; Afrianto, M F; Heriansyah, H; Nazaruddin, N; Nelson, N
Abstract: The biochar/TiO2 thin layer has been made by using the sol-gel method and the coating technique by Doctor Blade method. The variation of biochar on TiO2 were 0%, 1%, 2%, 3% and 4%. The characterization was done by using XRD (X-Ray Diffractometer) to see the crystal structure of samples and UV-Vis spectrophotometer to obtain the value of band gap energy . Based on XRD data, it was obtained that the crystal structure of all samples is anatase TiO2 . The crystalline size of all samples has no significant difference by the increasing of doping percentage. The smallest crystal size was at the addition of 3% and 4% bio char which was 118.22 nm. The results of UV-Vis characterization showed the lowest value of band gap energy was at sample doping 1% bio char which was 3.25 eV. Band gap energy value for doping sample above 1% showed an increase of band gap energy of Biochar-TiO2 .